Pengaruh Chatbot Marketing Quality Terhadap Customer Stickiness Melalui Social Presence, Perceived Warmth, dan Rapport Sebagai Variabel Intervening - Farah Aisha; Aflit Nuryulia Praswati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of chatbot marketing quality on customer stickiness with social presence, perceived warmth, and rapport as intervening variables, in e-commerce chatbot services in Indonesia. In this context, the quality of chatbot marketing is seen as a key factor that can shape customer attachment, both directly and through social and emotional perceptions during interactions. This study uses a quantitative approach with a survey method that was distributed online to 250 respondents who had used chatbot services on e-commerce platforms such as Shopee, TikTok Shop, Tokopedia, Lazada and Zalora. The sampling technique was carried out using the purposive sampling method, while the data analysis was carried out using the SEM-PLS method with the help of SmartPLS software version 3.0. The results of the study show that chatbot marketing quality has a positive and significant effect on social presence, perceived warmth, and rapport, which then has a positive impact on customer stickiness. These three intervening variables have also been shown to mediate the relationship between chatbot quality and customer attachment. These findings imply that the development of quality chatbots not only improves service efficiency, but can also build a more humane and enjoyable interaction experience, which ultimately strengthens customer loyalty to e-commerce platforms. This research is expected to be a reference in the development of digital technology-based marketing strategies in the e-commerce sector.